Research Regarding The Interaction Between Herpesviruses And Bacterial Agents In Aggressive Periodontitis Etiopathogeny - Mihaela Simona Grigoras; Ioana Rudnic; Catalina Danila; Oana Potârniche; Silvia Martu (Romanian Society of Oral Rehabilitation, 2013)
Introduction and purpose of the study Recent studies have proved that herpes viruses are involved in the aggressive periodontitis aetiology. The present study analyses if the presence of viruses in the aggressive periodontitis lesions is associated with periodontal pathogenic bacterial agents. Material and method The study was conducted on 16 subjects divided in two groups: a group of 11 subjects with aggressive periodontitis (study group) and a second group, formed by 5 periodontal healthy subjects (control group). The samples were collected from the gingival sulcus with paper cones. The qualitative identification of bacterial agents was conducted by molecular techniques such as PCR. Results HCMV, EBV-1 and HSV-1 viruses have been identified in a 72-78% percentage on patients with aggressive periodontitis. The obtained date indicated positive associations of herpes viruses with Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia. Instead, Aggregatibacter actinomycetemcomitans was not detected with HCMV, EBV-1 and HSV-1 in periodontal situses. Conclusions The results sustain the hypothesis that the clinical situation of certain severe periodontal infections depends on the specific presence of herpesviruses and pathogens. Our findings lead to further testing of hypothesis regarding the association between viruses and bacterial agents in periodontal affected situses.